2005
DOI: 10.1001/archinte.165.22.2631
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Diabetes Care

Abstract: Patients with mental illness merit special attention in national diabetes quality improvement efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(73 citation statements)
references
References 63 publications
4
68
1
Order By: Relevance
“…Furthermore, the risk of metabolic syndrome is estimated to be twofold higher, and the prevalence of DM2 three-to fivefold higher than the general population , De Hert et al 2006. Despite these implications, those with serious mental illness and DM2 are insufficiently monitored and undertreated (Frayne et al 2005, Kreyenbuhl et al 2006, Goldberg et al 2007. Moreover, mortality among those with serious mental illness and DM2 is higher than in those diagnosed with DM2 or serious mental illness alone (Jackson et al 2007, Vinogradova et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the risk of metabolic syndrome is estimated to be twofold higher, and the prevalence of DM2 three-to fivefold higher than the general population , De Hert et al 2006. Despite these implications, those with serious mental illness and DM2 are insufficiently monitored and undertreated (Frayne et al 2005, Kreyenbuhl et al 2006, Goldberg et al 2007. Moreover, mortality among those with serious mental illness and DM2 is higher than in those diagnosed with DM2 or serious mental illness alone (Jackson et al 2007, Vinogradova et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent systematic review on the quality of health care of physical illnesses in mentally ill patients, compared to those without mental illness, showed that most of the studies found inequity. 1 These studies emanated predominantly from the US, as well from the UK, Finland, and the Netherlands [2][3][4][5][6][7][8][9] and, for the most part, they were secondary evaluations of routine data. There is also a scarcity of studies surrounding other socially stigmatising diseases such as schizophrenia or depression.…”
Section: Introductionmentioning
confidence: 99%
“…However, healthcare disparities exist even for adults with serious mental illnesses who receive medical care [9][10][11][12][13][14] and physicians may be reluctant to treat patients with mental illnesses, inclined to misattribute physical complaints to their psychiatric illnesses, and underestimate the presence of medical disorders in these patients [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%